POSITIONING OF UKRAINE IN MODERN INTERNATIONAL MIGRATION PROCESSES - Kalinina, S. P.; Lanska, S. P.; Podunai, V. V. (The actual problems of regional economy development, 2024)
The article is devoted to the actual determination of Ukraine’s actual positioning in modern migration processes. It was emphasized that due to the full-scale war, the number of Ukrainian migrants around the world is constantly increasing, which leads to a decrease in the workforce in the national labor market. It has been established that over the past 30 years there has been an increase in emigration from Ukraine to middle-income countries, with a gradual increase in the flow to high-income countries. It is summarized that high level of emigration or labor export create significant risks for the effectiveness of socio-economic and socio-political transformations. For Ukraine this is particularly relevant, because of the talents outflow, which has increased significantly during 2022-2023. This will have a significant negative impact on society and economy. Attention is drawn to the fact that besides the fact of high rates of emigration, Ukraine is also one of the world's centers of attraction for migrants: before the full-scale invasion, there was a steady increase in both labor immigrants and students, the majority of whom came to Ukraine from the post-soviet countries of Central Asia, India and China. The expediency of restoring and supporting this human flow for the post-war recovery of Ukraine has been determined. An analysis of the employment indicators of Ukrainian refugees to the OECD countries was carried out. It was determined that due to the introduction of special schemes and political measures in most countries, Ukrainians got the opportunity to look for work at an earlier stage than other waves of refugees. This led to extremely high employment rates among Ukrainian migrants in some European countries. A general conclusion was made that at the current stage, Ukraine's participation in international migration processes mainly increases the labor shortage in the national labor market due to the high rate of emigration. The level of employment of Ukrainian migrants in Europe indicates a high degree of their integration in a new place, which actualizes the issue of non-return. Attention was drawn to the fact that for the effective functioning of the national labor market, Ukraine needs an up-to-date, effective and professionally oriented migration policy that can ensure the effective post-war recovery of the country's economy.